The HSP40 chaperone Ydj1 drives amyloid beta 42 toxicity. Issue 5 (4th April 2022) - Ring, Julia; Tadic, Jelena; Ristic, Selena; Poglitsch, Michael; Bergmann, Martina; Radic, Nemanja; Mossmann, Dirk; Liang, YongTian; Maglione, Marta; Jerkovic, Andrea; Hajiraissi, Roozbeh; Hanke, Marcel; et al.
Abstract: Amyloid beta 42 (Abeta42) is the principal trigger of neurodegeneration during Alzheimer's disease (AD). However, the etiology of its noxious cellular effects remains elusive. In a combinatory genetic and proteomic approach using a yeast model to study aspects of intracellular Abeta42 toxicity, we here identify the HSP40 family member Ydj1, the yeast orthologue of human DnaJA1, as a crucial factor in Abeta42‐mediated cell death. We demonstrate that Ydj1/DnaJA1 physically interacts with Abeta42 (in yeast and mouse), stabilizes Abeta42 oligomers, and mediates their translocation to mitochondria. Consequently, deletion of YDJ1 strongly reduces co‐purification of Abeta42 with mitochondria and prevents Abeta42‐induced mitochondria‐dependent cell death. Consistently, purified DnaJ chaperone delays Abeta42 fibrillization in vitro, and heterologous expression of human DnaJA1 induces formation of Abeta42 oligomers and their deleterious translocation to mitochondria in vivo . Finally, downregulation of the Ydj1 fly homologue, Droj2, improves stress resistance, mitochondrial morphology, and memory performance in a Drosophila melanogaster AD model. These data reveal an unexpected and detrimental role for specific HSP40s in promoting hallmarks of Abeta42 toxicity. Synopsis: This study reports a causal link between the heat shock protein 40 (HSP40) family member Ydj1/DnaJA1 and amyloid beta 42 (Abeta42) toxicity with potential implications to Alzheimer's disease (AD). By using AD models, Ydj1/DnaJA1 was found to drive Abeta42 pathology cascades. In yeast, Abeta42 forms toxic oligomers, which translocate to mitochondria and induce mitochondria‐dependent cell death. Mitochondrial proteomics and genetic screening reveal Ydj1 as a key player in Abeta oligomerization, mitochondrial translocation, and toxicity. Ydj1 and its human homologue DnaJA1 physically interact with Abeta and stabilize toxic Abeta oligomers. Depletion of the Drosophila melanogaster Ydj1 homologue, DroJ2, protects from Abeta42‐induced toxicity and improves memory performance in a fly model for AD. Human DnaJA1 is dysregulated in postmortem hippocampal tissue of AD patients. Abstract : This study reports a causal link between the heat shock protein 40 (HSP40) family member Ydj1/DnaJA1 and amyloid beta 42 (Abeta42) toxicity with potential implications to Alzheimer's disease (AD). By using AD models, Ydj1/DnaJA1 was found to drive Abeta42 pathology cascades.